Efek Hari Libur Lebaran Pada Emiten Yang Terdaftar Dalam ISSI Periode 2011-2013 - Utomo, Venny Julia (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to analyze the market reactions of Eid Mubarak Holiday which is indicated by the presence of average abnormal return and average abnormal trading volume activity on issuers in ISSI list within 2011-2013 period, and especially for the issuers which engaged in the field of food and drinking product industries, also retail industries as well.The method used in this research is event study which will analyze the alteration of price movements and volume of stock trading before and after Eid Mubarak Holiday. The hypothesis of this research is the presence of trading reaction that indicated by average normal return and the difference of average abnormal trading volume activity before and after Eid Mubarak Holiday. This research testing uses one sample-test to seek if there are any average normal returns around Eid Mubarak Holiday, while paired sample-test is used to test the difference of average normal trading volume activity before and after Eid Mubarak Holiday. The writer did the research within 41 days, divided into two periods. 30 days before Eid Mubarak Holiday and 10 days after Eid Mubarak Holiday. The amount of sample in this research is 31 issuers which have met the sampling criteria using purposive sampling.The result of the first hypothesis indicates that there is insignificant average abnormal return, while the second hypothesis indicates the difference of significant average abnormal trading volume activity.